2012
DOI: 10.1258/mi.2011.011117
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative inquiry into women's menopause experiences in southeastern Iran

Abstract: Menopause is defined as amenorrhea for one year. Signs and symptoms are categorized as physical and psychological changes, including depression, hot flushes and ageing. Woman's responses to menopause are governed by lifestyle factors. The purpose of this study was to determine how Iranian women experience menopause and hormone therapy. A qualitative inquiry was conducted through semistructured, in-depth interviews to explore study questions in 11 menopausal women. Participants had positive and negative menopau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Generally, gender inequality can be seen in different aspects of life in developing countries including sexual life. On the other hand, some studies reported menopause as a positive experience due to the cessation of bleeding and secretions, the reduced risk of pregnancy, and the possibility of participating in religious ceremonies [38]; the last was also seen in the present study.…”
Section: Plos Onesupporting
confidence: 73%
“…Generally, gender inequality can be seen in different aspects of life in developing countries including sexual life. On the other hand, some studies reported menopause as a positive experience due to the cessation of bleeding and secretions, the reduced risk of pregnancy, and the possibility of participating in religious ceremonies [38]; the last was also seen in the present study.…”
Section: Plos Onesupporting
confidence: 73%
“…It is largely due to entrenched traditional norms, values, cultural, and beliefs concerning sex and sexuality. 13 There has been some quantitative studies 14 15 16 and a few qualitative studies 17 18 19 on the subject of sexuality in Iranian menopausal women. Moreover, sexual issues are rooted in specific cultures and contexts, and the discovery of their associated issues demands requires exploring and appreciating problems in sociocultural context specific to Iranian society.…”
Section: Introductionmentioning
confidence: 99%
“…Iranian women’s concerns are about complications such as osteoporosis, sexual problems and aging (19). They also experience positive and negative changes during the menopause, and their negative experiences are associated with the severity of symptoms (20). …”
Section: Introductionmentioning
confidence: 99%